Adopsi Platform Gamified Learning Management System (GLMS) di Kelompok Usaha Bersama (KUB) Yasinta untuk Scaling Up Bisnis Desa - Arif Amrulloh; Rifki Adhitama; Ariq Cahya Wardhana; Galih Putra Pamungkas; Kholifahdina Kholifahdina; Martryatus Sofia; Izzaty Zahara BR. Barus (Pusat Riset dan Inovasi Nasional, 2025)
This community service activity aims to enhance the digital capacity and entrepreneurial skills of MSME actors who are members of the Yasinta Joint Business Group (Kelompok Usaha Bersama – KUB) through the adoption of a Gamified Learning Management System (LMS) platform. The methods used include a participatory approach, interactive training, and technology-based mentoring. The results of the activity indicate an improvement in participants’ understanding of business digitalization, increased learning motivation through gamification features, and enhanced ability to access and utilize the LMS for business management. This approach has proven effective as a technology-based community empowerment effort in rural areas.